Entrepreneurial Cognition Exploring the Mindset of Entrepreneurs - Shepherd, Dean A. (Springer Nature, 2018)
entrepreneurial mindset; cognitive processes; cognitive psychology; prior knowledge; exploitation; motivation; financial motivation; non-financial motivation; entrepreneurial opportunities; self-identity; well-being; work identity